INTER-TEXTUAL RELATIONSHIPS IN THE EPIC OF KÖROĞLU - Mehmet Emin BARS (Fırat University, 2019)
Today, Turkish clans that are spread out a very broad geography from middle Asia to Balkans have an epic tradition, based on a long past. Some of the epical tellings are in common in Turkish clans. Some of these tellings have reached today by being told some of them in written, some both written and oral, some in only oral tradition. One of the epics, living in oral tradition and having been reached today is the epic of Köroğlu. Köroğlu has an important place in the history of Turkish culture. Köroglu term, the symbol of power, has taken its place among the large groups of people especially because it is accepted as the representative of the power which is the supportive of the oppressed.Today, Köroglu epic has appeared in two versions and developing numerous variants as a result of spreading out, evolutions and their subsidiaries, the wealth gained by means of the narrative tradition through time and place. The concept of inter-textuality is a concept put forward by some critics in the 1960’s. The concept started to be widely used after the adoption of the idea of an autonomous text. The concept, in particular so-called postmodern works of the representatives of the new book finds a wide range of applications. Inter-textuality is a theory that looks for reports of texts, written before and interrogates the possible reading kinds and ways of texts in literary texts. Inter-textuality is based on the theory that a work can not be independent from other works. A work can’t be completely original as every work is in close relationship with another work and this interaction lasts forever. In our article “The Epic of Köroğlu” is studied according to the inter-textual relationships.